Процессы в околоземном космосе, сопровождавшие магнитную бурю 1 октября 2002 года - Пазюра, С. А.; Черняк, Ю. В. (НТУ "ХПИ", 2003)
Abstract Parameters variations researches results of ionosphere, which accompanied a magnetic storm with the main phase on October 1, 2002, performed on the Kharkov incoherent scatter radar are presented. According to time variations of concentration, speed, ion temperature of solar wind, induction module variation of IMF measured on artificial satellite "ACE" the picture of the sudden beginning, and also courses of an ionospheres storm is restored
Keywords: геокосмические бури; земная магнитосфера; атмосферные бури; ионосферные бури; магнитные бури; ионосфера; солнечный ветр